The influence of the El Niño Southern Oscillation on heat waves in India. (October 2016) - Murari, Kamal Kumar; Sahana, A. S.; Daly, Edoardo; Ghosh, Subimal
ABSTRACT: The present study investigated the relationship between the El Niño Southern Oscillation (ENSO) and heat wave characteristics, such as duration, annual number of heat wave days and maximum temperature of heat wave events, in India. El Niño is associated with an eastward shift in the Walker circulation and breakdown of circulation patterns, resulting in delay in the onset of the Indian Summer Monsoon (ISM). Because most heat waves in India occur during the pre‐monsoon season, the present study showed that heat waves during El Niño years were longer and hotter, and it is argued that this is related to a delay in the onset of the ISM. Further, it was found that the shift in the circulation pattern due to El Niño resulted in (1) the weakening of southwesterlies in the Arabian Sea, and (2) the occurrence of a large number of clear sky days over India. These explain the occurrence of warmer and longer duration heat waves during El Niño years. These results imply that, if El Niño activity increases in the future, heat waves in India are likely to intensify.